Analisis Tingkat Pengadaan Bahan Baku Pembuatan Kerupuk pada PT XYZ - Firmansyah, Roziq; Putu Eka Dewi Karunia Wati (Fakultas Teknik UMRI, 2024)
PT XYZ is a cracker producer and exporter in Sidoarjo facing difficulties in managing raw materials. Strategic procurement management is crucial for timely availability, production optimization, and reducing stock depletion risks. Fluctuating demand patterns and declining supplier performance during the rainy season result in suboptimal stock levels. The research involves demand data, warehouse capacity, and procurement. Findings indicate a warehouse capacity of 55-60 tons, mostly for shrimp flour. High demand from January to May requires 45-65 tons of shrimp flour, 20-35 tons of plain flour, and 10-20 tons of lombok flour. An appropriate procurement strategy considering warehouse capacity and supplier capabilities is necessary. Analyzing supplier payments through sales flow enhances understanding of stock needs and purchasing planning.